Meteoric CaO and carbon smoke particles collected in the upper stratosphere from an unanticipated source - Alessandra Rotundi; M. Ferrari; Pasquale Palumbo; F. J. M. Rietmeijer; Vincenzo Della Corte (Tellus B: Chemical and Physical Meteorology, 2013)
Nanometre CaO and pure carbon smoke particles were collected at 38-km altitude in the upper stratosphere in the Arctic during June 2008 using DUSTER (Dust in the Upper Stratosphere Tracking Experiment and Retrieval). This balloon-borne instrument was designed for non-destructive collection of solid particles between 200 nm to 40 µm. We report here on micrometre CaCO 3 (calcite) grains with evidence of thermal erosion and smoke particles that formed after melting and vaporisation and complete dissociation of some of the CaCO 3 grains at temperatures of approximately 3500 K. These conditions and processes suggest that the environment of this dust was a dense dust cloud that had formed after disintegration of a carbonaceous meteoroid during deceleration in the atmosphere. The balloon-borne collector must have coincidentally travelled through the dust cloud of a recent bolide event that had penetrated between 38.5 and 37 km altitude. This work identified a previously unknown meteoric smoke forming process in addition to meteoric smoke particles due to photolysis-driven oxidation of mesospheric metals from meteor ablation that had settled into the upper stratosphere. Keywords: meteoric smoke, carbonaceous meteorites, stratospheric dust, laboratory analyses, chemical compostion (Published: 18 July 2013) Citation: Tellus B 2013, 65 , 20174, http://dx.doi.org/10.3402/tellusb.v65i0.20174